Criticism of common sense in light of contemporary physics in general and quantum physics in particular - شعيبي, عماد فوزي; الخطاب, ريم جمال (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Quantum physics is one of the many controversial patterns of contemporary physics, which has long debates of length and differing opinions that are difficult to sum up, in science as in philosophy, and in their philosophy. This research is an approach aimed at reviewing some of the problems posed by quantum physics according to a synthetic analytical method as possible. Quantum physics has changed the stereotype of science, as these physics have spread concepts such as Subjectivity, undetermine and Probability truth, and have focused on the importance of aesthetic considerations and the value of intuition in building and developing science. What led to the result of an epistemological Rapture with the previous way of science. One of its results was the attempts of many supporters of quantum to Criticism of common sense, and the establishment of a philosophy of science based on separation from the prevailing and entrenched in our human thought, which accumulated until it seemed to be a kind of common unconscious among humans, or A pattern of collective unconscious Which we believe it intuitively. This necessitated the question about What's called dialectical relationship that arose later between quantum and science and its philosophy, and the Effects of this relationship. Quantum, in its approach to the concept of truth and its attempt to explain the origin of the universe, allows us to see it in some aspects, or read it as a metaphysical philosophical theory, which in turn calls into question the extent of its separation or its compatibility with the outputs of common sense and its postulates.